The Effectiveness of the "Desa SIAP" Website in Improving Public Services in Leran Village, Manyar District, Gresik Regency - Chanifah, Siti; Widiyarta, Agus (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The “Desa SIAP” website (Sistem Informasi Administrasi Pemerintahan Desa) is a digital platform used by the Leran Village Government to facilitate online public services. Through this website, villagers can acces information related to village government, make administrative submissions such as official papers, and see the transparency of the village budget and public information. This study aims to describe and analyze the effectiveness of e-government through the “Desa SIAP” website in Leran Village, Manyar District, Gresik Regency. The focus of this research uses Duncan's theory, including: goal achievement, integration, and adaptation. This study uses a descriptive qualitative approach with data collection techniques using interviews, documentation, and field observations. The results of the study show that the effectiveness of E-Government through the "Desa SIAP" Website in Improving Public Services in Leran Village, Manyar District, Gresik Regency has been effective and running well. The achievement of the goal has been done well, where the “Desa SIAP” website has increased the efficiency, transparency, and accessibility of services in Leran Village, but education and assistance are still needed for people who do not understand technology. The integration of the “Desa SIAP” website is quite effective with easy socialization and procedures, but further strategies are needed so that the community better understands and uses the website well. The adaptation to the implementation of the “Desa SIAP” website has gone well, supported by the ability of trained employees and adequate infrastructure.